Smile of the Universe: Miracles in an Age of Disbelief by Michael Grosso - Hayen, Todd (Journal of Scientific Exploration, 2022)
Smile of the Universe (2020) by Michael Grosso is a delightful book filled with magic and intrigue for the inquisitive reader. Grosso starts our journey with citing many historical events that have been deemed “miraculous” not only by the Catholic church, which seems to have had the corner on miracles since the Church’s beginnings, but also those that fall out of the realm of organized religion. What made this book delightful for me is that Grosso’s own particular interest in miracles resonates with mine, and I am fairly certain will resonate with many other readers. In the opening pages of Grosso’s book he immediately makes it clear that he personally has experienced a miracle, several in fact. The reader then knows that this book is not just a documentation of dry historical events, but rather of a topic that presents phenomena that the author himself has been personal witness to. We are immediately engaged in both the subjective and the objective: story telling at its best. And what are miracles but human stories created around a set of unexplainable material events? A dream, what most believe to be pure subjective containing no material substance at all, is not considered a miracle. But if that dream manifests in material form, then indeed it becomes miraculous. Not all miracles are first dreams of course, but all miracles do have a material construct, and what makes them a miracle is their stubbornness in ignoring the set, presently known, laws of nature.